Ketahanan Pangan Rumah Tangga di Kecamatan Jaro Kabupaten Tabalong, Kalimantan Selatan - Ahmad Suhaimi (LPPM Sekolah Tinggi Ilmu Pertanian Amuntai, 2015)
This study aims to assess household food security, social and economicsfactors that affect household food security and knowing the dominant factor in household food security in the village of Namun, Jaro District of Tabalong regency. The level of household food security is dominated by a group of food enough that 30 households or by 40% and 29 household food security by presenting 38.67%. Groups that are not food secure are 16 households or 21.33%. Groups of households have food secure rice supplies between 120-239 days with eating frequency of household members 3 times a day. F test analysis results obtained value of 2.431> F table value of 2.346 at odds of 0.05 <0.05 means that all the variables in the equation simultaneously a significant effect on household food security. Results of t test analysis of socio-economics factors are the most dominant influence on household food security is a factor value income amounted to 2.058 t count> t table value of 1.667 with 0.041 odds <0.05. This suggests that factors ofincomesignificantly affect, but the number of family, the level of family Education, and expenditure, each no significant effect on household food security